Toxicological Insights Into Multiple Pesticide Exposures in Red Swamp Crayfish ( Procambarus clarkii ): Molecular Mechanisms, Risk Assessments, and Future Perspectives for Aquaculture - Dan‐Dan Bian; Zi‐Yi Xing; Shuang‐Gui Dai; Xiang Lu; Dai‐Zhen Zhang; Bo‐Ping Tang; Bao‐Jian Zhu; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
The rice–crayfish integrated system (RCIS) is vital to Asian aquaculture, yet its sustainability is threatened by a critical paradox: pesticides used in rice cultivation jeopardize the health of the red swamp crayfish ( Procambarus clarkii ) and the safety of its products. This review systematically synthesizes evidence establishing oxidative stress as the central hub linking pesticide exposure to multilevel toxicity in P. clarkii . We delineate how pesticides dysregulate key pathways (PI3K/AKT/mTOR, MAPK, NF‐κB), triggering apoptosis, metabolic disruption, and immunosuppression. A pivotal mechanism involves pesticide‐induced gut microbiota dysbiosis, which diminishes beneficial short‐chain fatty acids and enriches pathogens, thereby amplifying intestinal barrier damage and host vulnerability. These interconnected processes collectively stunt growth and heighten susceptibility to pathogens like white spot syndrome virus (WSSV). Beyond organismal effects, we evaluate environmental pesticide fate and propose a novel risk assessment framework integrating these sublethal endpoints. Our proposed mitigation strategies include eco‐friendly pesticides, ecological engineering, and microbiome‐directed interventions. We advocate for future research prioritizing multi‐omics and mixture toxicity assessment. By deciphering this toxicity cascade and translating insights into practice, this review aims to protect the productivity, ecological integrity, and food safety of integrated aquaculture systems for long‐term sustainability.